Spectrum of the neurologic manifestations in childhood-onset cryopyrin-associated periodic syndrome. (May 2019) - Kilic, Huseyin; Sahin, Sezgin; Duman, Cisem; Adrovic, Amra; Barut, Kenan; Turanli, Eda Tahir; Yildirim, Senihe Rengin; Kizilkilic, Osman; Kasapcopur, Ozgur; Saltik, Sema
Abstract: Objective: Neurologic complications of chronic infantile neurologic, cutaneous and articular syndrome (CINCA) are well-known, whereas there are scarce data regarding neurologic features of milder cryopyrin-associated periodic syndrome (CAPS) phenotypes. We aimed to review the neurologic features in detail and summarize the other CAPS-related manifestations in 12 children. Methods: All children with CAPS that have been followed-up from pediatric rheumatology outpatient clinic, were enrolled to the study. In addition to the neurologic examination, magnetic resonance imaging (MRI) of brain, electroencephalography, eye examination, hearing test and intellectual assessment were done. Demographic, clinical features, genetic analysis and laboratory tests were noted from patient records and hospital database. Results: The median age of the subjects was 7 years (range 2–19 years), with a female-to-male ratio 2/1. The phenotype was consistent with familial cold autoinflammatory syndrome in 7 patients, Muckle–Wells syndrome in 3 patients and chronic infantile neurologic, cutaneous and articular syndrome in 2 patients. Most frequently noted neurologic clinical manifestation during the entire disease course was headache (n = 4/12) followed by seizures (n = 3/12), papilledema (n = 3/12), intellectual disability (n = 2/12), aseptic meningitis (n = 2/12), hearing loss (n = 2/12) and optic atrophy (n = 1/12). MRI of the brain revealed abnormal lesions in two patients. Uveitis or conjunctivitis were seen in two children. Overall, neurological involvement was detected in 6/12 of our cohort, of which half (n = 3) was in severe form. Conclusion: Half of the children with CAPS exhibited neurologic manifestations with varying degrees of severity. Increased understanding and awareness of this rare but treatable syndrome among neurologists is essential. If remains untreated and unrecognized, this autoinflammatory syndrome could lead to significant morbidity and mortality. Besides complete resolution of systemic symptoms, anti-interleukin-1 treatment may also prevent progression of neurologic findings when initiated in the early stage of the disease. Highlights: CAPS is an autoinflammatory syndrome with frequent neurological manifestations. Management of this multisystemic disease requires a team approach. Delayed diagnosis leads to significant morbidity and mortality. Increased awareness of this rare but treatable IL1-associated disease is essential.